Race, ethnicity and COVID-19 vaccination: a qualitative study of UK healthcare staff. Issue 7 (3rd October 2022) - Woodhead, Charlotte; Onwumere, Juliana; Rhead, Rebecca; Bora-White, Monalisa; Chui, Zoe; Clifford, Naomi; Connor, Luke; Gunasinghe, Cerisse; Harwood, Hannah; Meriez, Paula; Mir, Ghazala; Jones Nielsen, Jessica; et al.
ABSTRACT: Objective: COVID-19-related inequities experienced by racial and ethnic minority groups including healthcare professionals mirror wider health inequities, which risk being perpetuated by lower uptake of vaccination. We aim to better understand lower uptake among racial and ethnic minority staff groups to inform initiatives to enhance uptake. Design: Twenty-five semi-structured interviews were conducted (October 2020–January 2021) with UK-based healthcare staff. Data were inductively and thematically analysed. Results: Vaccine decision-making processes were underpinned by an overarching theme, 'weighing up risks of harm against potential benefits to self and others'. Sub-themes included 'fear of harm', 'moral/ethical objections', 'potential benefits to self and others', 'information and misinformation', and 'institutional or workplace pressure'. We identified ways in which these were weighted more heavily towards vaccine hesitancy for racial and ethnic minority staff groups influenced by perceptions about institutional and structural discrimination. This included suspicions and fear around institutional pressure to be vaccinated, racial injustices in vaccine development and testing, religious or ethical concerns, and legitimacy and accessibility of vaccine messaging and communication. Conclusions: Drawing on a critical race perspective, we conclude that acknowledging historical and contemporary abuses of power is essential to avoid perpetuating and aggravating mistrust by de-contextualising hesitancy from the social processes affecting hesitancy, undermining efforts to increase vaccine uptake.